Flickering Polarons Extending over Ten Nanometres Mediate Charge Transport in High‐Mobility Organic Crystals. Issue 9 (6th July 2020) - Giannini, Samuele; Ziogos, Orestis George; Carof, Antoine; Ellis, Matthew; Blumberger, Jochen
Abstract: Progress in the design of high‐mobility organic semiconductors has been hampered by an incomplete fundamental understanding of the elusive charge carrier dynamics mediating electrical current in these materials. To address this problem, a novel fully atomistic non‐adiabatic molecular dynamics approach termed fragment orbital‐based surface hopping (FOB‐SH) that propagates the electron‐nuclear motion has been further improved and, for the first time, used to calculate the full 2D charge mobility tensor for the conductive planes of six structurally well characterized organic single crystals, in good agreement with available experimental data. The nature of the charge carrier in these materials is best described as a flickering polaron constantly changing shape and extensions under the influence of thermal disorder. Thermal intra‐band excitations from modestly delocalized band edge states (up to 5 nm or 10–20 molecules) to highly delocalized tail states (up to 10 nm or 40–60 molecules in the most conductive materials) give rise to short, ≈ 10 fs‐long bursts of the charge carrier wavefunction that drives the spatial displacement of the polaron, resulting in carrier diffusion and mobility. This study implies that key to the design of high‐mobility materials is a high density of strongly delocalized and thermally accessible tail states. Abstract : The full 2D charge mobility tensor is computed for the conductive planes of six organic semiconducting crystals using quantum–classical non‐adiabatic molecular dynamics simulation. The nature of the charge carrier in these materials is best described as a flickering polaron delocalized over several nanometers in the most conductive crystals and constantly changing shape and extensions under the influence of thermal disorder.